Influence of load-level and effective thickness on the fire resistance of composite slabs with steel deck - Santos, Lucas Manoel Cunha (2022)
Composite slabs with steel deck have been used on building construction due to its fast-and-easy crafting that brings economic outstanding alternatives to architects and engineers on large-scale steel framed constructions. At room temperatures and in Europe, the designing procedures of composite slabs are defined by Eurocode 1994-1-1. When it comes to the fire safety analysis of these elements, the designing procedure requires more attention due to the direct exposition of the steel deck to fire, affecting the overall bending resistance. This importance is presented in Eurocode 1994-1-2, taking in consideration the integrity, insulation and load-bearing criteria. In this work the thermal and mechanical behaviour of composite slabs with steel deck exposed to standard fire ISO 834 are studied through numerical simulations using Finite-Element Method (FEM). The model was previously validated with one experimental test from literature. The ANSYS Mechanical APDL software was used to develop a parametric study, simulating four different geometries with different load levels, comprehending a total of 126 thermal and mechanical simulations used to determine the correlation between load-level and fire resistance. As result, a new simplified method is proposed for the load bearing fire resistance of composite slabs, considering the effect of the effective thickness and the load level. The fire resistance decreases with the load level and increases with the thickness of the concrete. A new proposal is presented to determine the fire resistance, based on these two parameters.